Peningkatan Kompetensi Penyusunan Digitalisasi Bahan Ajar Bilingual bagi Guru Taman Kanak-Kanak - Khosiyono, Banun Havifah Cahyo; Nisa, Ana Fitrotun; Mulida, Alfiatul; Mulyantoro, Praja (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
This PKM activity aims to resolve existing problems with partners in order to support the efforts of the limited capacity group (KKG) of Masyitoh Al-Iman Kindergarten, Sewon, Bantul in preparing the digitization of bilingual-based teaching materials using online applications, so that the Bachelorwiyata Tamansiswa University collaborates with (KKG) Masyitoh Al-Iman Kindergarten to hold training for Kindergarten Teachers in preparing the digitization of bilingual-based teaching materials using online applications. This PKM activity aims to develop the competence of Kindergarten Teachers in compiling digitized bilingual-based teaching materials using online applications. The solution and method in this PKM program is to provide assistance and skills training to kindergarten teachers in Bantul district according to partner conditions so that partners will be able to have kindergarten teachers who are competent in preparing the digitization of bilingual-based teaching materials using online applications. The results of this activity were that the activity ran smoothly, the participants gained quite a lot of benefits, including gaining additional knowledge regarding good learning tools, as material for self-introspection to correct previously prepared learning tools, teachers were able to practice directly in compiling digitalized teaching materials billing based using online applications.